Analysis of Foot Sensation and Physical Activity in Diabetes Mellitus - Suyanto Suyanto; Uchrizal Febby Millenniantary; Mohammad Arifin Noor (Media Keperawatan Indonesia, 2022)
Neuropathy is a condition in which the patient experiences a decreased sensation of pain in the legs that can affect the physical activity of diabetic patients mellitus, until work productivity decreases. This pain is often disturbing, limiting activity and decreasing the work productivity of diabetic patients. The aim of this study was to identify a correlation between foot sensation and physical activity of diabetic mellitus patients.  cross-sectional was used in this study. Data collection uses instruments in the form of observation sheets to assess the results of foot sensation examination with a 10 gr monofilament test and IPAQ-SF (International Physical Activity Questionnaire Short Form) questionnaire sheet on 70 respondents with a purposive sampling technique. The data was processed using Kendall's Tau statistical test. A total of 70 respondents obtained an average age of 57 years, long-suffering from diabetes mellitus for an average of 4 years. 39 people received normal test results and 31 experienced decreased leg sensation and an average score of 5 with moderate physical activity categories. Gamma statistical test results p-value value 0.0001 or (p≤0.05) with a positive relationship direction and strangeness (r = -0.706). There is a relationship between decreased leg sensation and physical activity of diabetic mellitus patients at Bangetayu Health Center Semarang